Activation of Natural Zeolite Mixture and Coal Flyash Using Microwave as Air Filter for the Improvement of Gasoline Four-Stroke Motorcycle Engine Acceleration - Risano, A Yudi Eka; Wardono, Herry; Renardy, B Niko; Susila, M Dyan; Sugiri, Agus; Haviz, Muhammad (INSTEP Network, 2024)
Combustion is a chemical process between fuel and oxygen utilizing heat. Ambient air contains a variety of gases such as nitrogen, oxygen, and other gases, causing incomplete combustion in the combustion chamber of a 4-stroke petrol engine. The use of artificial air filters with zeolite-flyash composition activated by microwave can adsorb the air that enters the combustion chamber. So that it can improve the quality of combustion. Zeolite is a mineral that is found in limestone mountainous areas, while coal flyash is material from coal combustion at PLTU. Both of these materials have the ability to adsorb molecular sized particles such as nitrogen, CO and water vapor in the air, so the use of both materials is able to produce air with rich oxygen. The performance of the 4-stroke petrol engine is influenced by a decrease in fuel consumption, able to increase acceleration, and reduce exhaust emissions containing CO and HC. To find out the effect of the use of activated zeolite-flyash filters on engine performance, an acceleration test of 0-60 kph was performed. Filter being activated by Microwave with 80% power, 6 minutes activation time, and density (variation in the number of pellets in the filter) 50%, 75%, 100%, and use the Z0: F100, Z25: F75, Z50: F50, Z75: F25, Z100: F0. The best filter is the composition of Z100:F0 with a compactness of 50% able to increase acceleration by 7.17%, followed by filter with composition of Z25:F75 with a compactness of 50% able to increase acceleration by 4,04%.